The CLEAR model: a structured communication protocol for breast radiologists - Teresa Abbattista; Aram Hasan (Frontiers in Health Services, 2026)
Background Communication in diagnostic breast imaging remains a critical yet frequently neglected aspect of radiological training. Traditionally centered on technical image interpretation, radiological education often leaves practitioners unprepared to navigate the severe emotional and psychological burden of a suspected breast cancer diagnosis. Objectives This paper advocates for the communicative autonomy of the breast radiologist, arguing that direct, empathetic communication is not a secondary skill, but a core clinical act that directly influences both the psychological wellbeing and the physiological stress response of the patient. Methods We propose the CLEAR protocol ( Connect, Listen, Explain, Ask, Reassure ), a transcultural framework conceptualized to bridge clinical rigor with human empathy. The model integrates plausible neurobiological pathways—hypothesizing that non-verbal semiotics may influence HPA-axis regulation and facilitate oxytocin release—with the goal of potentially mitigating the acute “cognitive blackout” that patients may experience during diagnostic procedures. Key findings By structuring patient interaction, the CLEAR model could help patients regulate their acute stress response, preserving the patient's cognitive clarity and emotional resilience. Furthermore, by defining the radiologist's role within the multidisciplinary Breast Unit, the framework prevents the unproductive “chain of delegation” that frequently results in patient depersonalization. Conclusions Re-establishing the radiologist's communicative role is vital for the integrity and efficiency of the Breast Unit. Implementing structured frameworks like the CLEAR protocol ensures diagnostic precision while safeguarding the patient's emotional energy for their subsequent oncological care.